Short-term exercise training improves flow-mediated dilation and circulating angiogenic cell number in older sedentary adults - Landers-Ramos, Rian Q; Corrigan, Kelsey J; Guth, Lisa M; Altom, Christine N; Spangenburg, Espen E; Prior, Steven J; Hagberg, James M (Applied physiology, nutrition, and metabolism, 2016)
Cardiovascular disease risk increases with age due, in part, to impaired endothelial function and decreased circulating angiogenic cell (CAC) number and function. We sought to determine if 10 days of aerobic exercise training improves endothelial function, CAC number, and intracellular redox balance in older sedentary adults. Eleven healthy subjects (4 men, 7 women), 61 ± 2 years of age participated in 60 min of aerobic exercise at 70% maximal oxygen consumption for 10 consecutive days while maintaining body weight. Before and after training, endothelial function was measured as flow-mediated dilation of the brachial artery and fasting blood was drawn to enumerate 3 CAC subtypes. Intracellular reactive oxygen species (ROS) and nitric oxide (NO) in CD34+ CACs were measured using fluorescent probes and reinforced via real-time quantitative polymerase chain reaction. Flow-mediated dilation improved significantly following training (10% ± 1.3% before vs. 16% ± 1.4% after training; P < 0.05). Likewise, CD34+/KDR+ number increased 104% and KDR+ number increased 151% (P < 0.05 for both), although CD34+ number was not significantly altered (P > 0.05). Intracellular NO and ROS levels in CD34+ CACs were not different after training (P > 0.05 for both). Messenger RNA expression of SOD1, endothelial nitric oxide synthase, and NADPH oxidase 2 and neutrophil cytosolic factor 1 in CD34+ CACs was not significantly altered with training (P > 0.05). In conclusion, 10 consecutive days of aerobic exercise increased flow-mediated dilation and CAC number in older, previously sedentary adults, but did not affect intracellular redox balance in CD34+ CACs. Overall, these data indicate that even short-term aerobic exercise training can have a significant impact on cardiovascular disease risk factors.